Cost-benefit analysis of sport events: The case of World Paddle Tour - Héctor V. Jiménez-Naranjo; José Luis Coca-Pérez; Milagros Gutiérrez-Fernández; Mari Cruz Sánchez-Escobedo (European Research on Management and Business Economics (ERMBE), 2016)
Nowadays tourism is one of the most important sectors of our country, and no one has any doubt about importance of sport for the economy. Both concepts create “sports tourism”, and “sporting events” are its greatest exponent that is having special importance both at academic and at the economic and social levels. Taking into account the above, this research aims to analyze socioeconomic impact of the paddle tournament “Caceres International Open 2013”. The CBA methodology will be used; its main objective is to calculate a benefit/cost ratio analyzing the contribution made by two groups of respondents (attendees and participants). Among final conclusions of this study we establish different groups of stakeholders, and this methodology can be applied to these groups to value the impact of sporting events. It has also been found out that the contribution made by public institutions has economic effects in other sectors of the city; so sporting events can be considered a complement of the tourism sector. – – En la actualidad el sector turístico es uno de los sectores más importantes de nuestro país, además hoy en día nadie duda de la gran importancia que tiene el deporte en la economía. Ambos conceptos originan el “Turismo Deportivo” cuyo máximo exponente son los “eventos deportivos” que en los últimos a\~nos está teniendo especial relevancia tanto en el ámbito académico como en el económico y social. Considerando lo anterior, la presente investigación tiene como finalidad realizar un análisis del impacto socioeconómico deltorneo de Pádel “Cáceres International Open 2013”. Para ello, se aplicará lametodología ACB, cuyo principal objetivo es la obtención de una ratio beneficio-coste analizando la contribución que han realizado los encuestados al evento (asistentes y participantes). Entre las conclusiones obtenidas, este estudio aporta los diferentes grupos de interés sobre los que aplicar la metodología para la valoración del impacto en los eventos deportivos. Además se ha constatado que la aportación realizada por parte de las instituciones públicas tiene efectos económicos en otros sectores de la ciudad, de manera que los eventos deportivos pueden ser considerados como un complemento del sector turístico.
Keywords: A13; C67; L83; 650; Economic impact; Social impact; Cost/benefit analysis; Sports tourism; Impacto económico; Impacto social; Análisis coste beneficio; Turismo deportivo